The effects of fibre content on flexural and impact properties of woven sugar palm fibre reinforced unsaturated polyester composites - Ishak, Mohamad Ridzwan; Leman, Zulkiflle; Salit, Mohd Sapuan; Misri, Sairizal (2009)
The main advantages of the sugar palm fibres are their high durability, resistance to sea water and ease of processing where the fibres do not require any secondary process to yield the fibres. This study investigates the effects of fibres content on the flexural and impact properties of woven sugar palm fibres reinforced unsaturated polyester composite. The composite specimens made of different fibre weight contents of 13% (1 layer), 18% (2 layers), 22% (3 layers) and 29% (4 layers) of woven sugar palm fibres were prepared. The flexural and impact tests were carried out in accordance to ASTM D790 and ASTM D256 respectively. One-way ANOVA and Duncan multiple range test were used for statistical analysis. The results showed that the fibre content had significant effects on the flexural strength and impact strength of the composites with the exception of flexural modulus.